ANALISIS MULTIMODAL WACANA KRITIS REKLAME POLITIK BAKAL CALON PRESIDEN REPUBLIK INDONESIA 2024 - Syah, Saprudin Padlil; Syah, Abdul Jabbar Siddiq; Syah, Abdulloh Jalaluddin (Widyaparwa, 2024)
In 2023, the billboards of the three presidential candidates for the Republic of Indonesia in 2024 have spread in several regions in Indonesia. The billboard as a political discourse does not only show words or images, but also has a meaning behind it. This research aims to explore the meaning behind the political billboards of the 2024 presidential candidates: Anies Baswedan, Ganjar Pranowo, and Prabowo Subianto. This research uses descriptive qualitative method. The data in this study are political billboards of three 2024 presidential candidates of the Republic of Indonesia with online media data sources. The data is obtained through internet searches that have appeared since 2023 and analyzed with Fairclough's analysis through three stages, namely textual dimensions, analysis of discourse practices, and analysis of sociocultural practices which in the analysis of textual dimensions, this research will apply Anstey and Bull's multimodal analysis. Based on the research, it is known that the following conclusions can be formulated. First, the billboards of Anies, Ganjar, and Prabowo have different political meanings based on textual analysis, discourse practice analysis, and sociocultural practice analysis. Second, the Anies presidential billboard shows the implied ideology and power relations between Anies, the billboard maker, and supporting parties; the Ganjar presidential billboard also shows the implied ideology and power relations between Ganjar, the billboard maker, and supporting parties; the Prabowo presidential billboard also shows the implied ideology, but only shows the power relations between two parties, namely Prabowo and the billboard maker.Pada tahun 2023 reklame pencapresan tiga bakal calon presiden Republik Indonesia tahun 2024 sudah tersebar di beberapa wilayah di Indonesia. Reklame tersebut sebagai sebuah wacana politik tidak hanya memperlihatkan kata-kata atau gambar saja, tetapi juga mempunyai makna di baliknya. Penelitian ini bertujuan untuk menggali makna di balik reklame politik bakal calon presiden Republik Indonesia tahun 2024: Anies Baswedan, Ganjar Pranowo, dan Prabowo Subianto. Penelitian ini menggunakan metode kualitatif deskriptif. Data dalam penelitian ini adalah reklame politik tiga bakal calon presiden Republik Indonesia 2024 dengan sumber data media daring. Data didapat melalui pencarian di internet yang muncul sejak 2023 dan dianalisis dengan analisis Fairclough melalui tiga tahap, yaitu dimensi tekstual, analisis praktik kewacanaan, dan analisis praktik sosiokultural yang pada analisis dimensi tekstual, penelitian ini akan menerapkan analisis multimodal Anstey dan Bull. Berdasarkan penelitian, diketahui bahwa dapat dirumuskan simpulan sebagai berikut. Pertama, reklame pencapresan Anies, Ganjar, dan Prabowo mempunyai makna politik yang berbeda berdasarkan analisis tekstual, analisis praktik kewacanaan, dan analisis praktik sosiokultural. Kedua, pada reklame pencapresan Anies tersirat adanya ideologi dan relasi kuasa di antara Anies, pembuat reklame, dan partai pendukung; pada reklame pencapresan Ganjar tersirat adanya ideologi dan adanya relasi kuasa di antara Ganjar, pembuat reklame, dan partai pendukung; pada reklame pencapresan Prabowo pun tersirat adanya ideologi, tetapi hanya menunjukkan relasi kuasa antara dua pihak, yaitu Prabowo dan pembuat reklame.